Fairness in a Society of Unequal Opportunities - Alexander W. Cappelen; Yiming Liu; Hedda Nielsen; Bertil Tungodden (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2024)
Modern societies are characterized by widespread disparities in opportunities, which play a crucial role in creating income inequality. This paper investigates how individuals handle income inequality arising from these unequal opportunities. We report from a large-scale experimental study involving general populations in the United States and Scandinavia, where participants make consequential redistributive decisions as third-party 'spectators' for workers who faced unequal opportunities. Our findings provide strong evidence that a significant majority of people are willing to accept inequality caused by unequal opportunities, a position that markedly contrasts with their responses to inequality caused by luck. Two distinct forces drive greater acceptance of inequality under unequal opportunities: the tendency to mistakenly attribute the impact of unequal opportunities to inherent productivity, and the moral relevance attributed to choice differences caused by unequal opportunities. We further demonstrate a clear societal and political divide in responses to unequal opportunities, with Americans and right-wing voters exhibiting a greater acceptance of the resulting inequality, reflecting both differences in fairness views and attribution biases in these populations.
Keywords: 330; Unequal opportunities; Inequality acceptance; Attribution bias; Fairness views